Chronic 5-Aminoimidazole-4-Carboxamide-1-β-d-Ribofuranoside Treatment Induces Phenotypic Changes in Skeletal Muscle, but Does Not Improve Disease Outcomes in the R6/2 Mouse Model of Huntington’s Disease - Paré, Marie-France; Jasmin, Bernard J. (Frontiers in Neurology, 2017)
Huntington’s disease (HD) is an autosomal dominant neurodegenerative genetic disorder characterized by motor, cognitive and psychiatric symptoms. It is well established that regular physical activity supports brain health, benefiting cognitive function, mental health as well as brain structure and plasticity. Exercise mimetics (EMs) are a group of drugs and small molecules that target signaling pathways in skeletal muscle known to be activated by endurance exercise. The EM 5-aminoimidazole-4-carboxamide-1-β-D-ribofuranoside (AICAR) has been shown to induce cognitive benefits in healthy mice. Since AICAR does not readily cross the blood-brain barrier, its beneficial effect on the brain has been ascribed to its impact on skeletal muscle. Our objective, therefore, was to examine the effect of chronic AICAR treatment on the muscular and neurological pathology in a mouse model of HD. To this end, R6/2 mice were treated with AICAR for 8 weeks and underwent regular neurobehavioral testing. Under our conditions, AICAR increased expression of PGC-1α, a powerful phenotypic modifier of muscle, and induced the expected shift towards a more oxidative muscle phenotype in R6/2 mice. However, this treatment failed to induce benefits on HD progression. Indeed, neurobehavioral deficits, striatal and muscle mHTT aggregate density, as well as muscle atrophy were not mitigated by the chronic administration of AICAR. Although the muscle adaptations seen in HD mice following AICAR treatment may still provide therapeutically relevant benefits to patients with limited mobility, our findings indicate that under our experimental conditions, AICAR had no effect on several hallmarks of HD.